Cultivating Scientific Leadership: A Strategic Imperative for Ethiopian Applied Universities in the 21st Century - Belay Sitotaw Goshu (Budapest International Research and Critics University, 2026)
Ethiopian applied universities have expanded rapidly over the past two decades, yet institutional leadership often undervalues scientific research, undermining innovation capacity and alignment with national development goals. This article argues that cultivating scientific leadership defined as leaders’ capacity to value, invest in, and strategically leverage science is a strategic imperative for Ethiopian applied universities in the 21st century. Drawing on literature from higher education leadership, science policy, and Ethiopian educational development, this conceptual analysis synthesizes empirical evidence from cited studies and policy documents to examine barriers and propose strategic pathways. The analysis reveals four principal findings: (1) leadership structures undervalue research despite STI policy commitments; (2) student–staff ratios averaging 75.9:1 constrain faculty research engagement; (3) institutional KPIs allocate only 8% weight to research metrics; and (4) industry linkages remain dominated by internships (95%) rather than R&D partnerships (20%). Cultivating scientific leadership requires phased governance reforms, aligned incentives, immersive leadership development, and cultural transformation. Policymakers and institutional leaders must prioritize research capacity building, restructure governance to elevate scientific expertise, and realign performance metrics to reward research productivity.